Construction of an Intensive Training Program for Badminton Reserve Players Before Team Selection Match - Chen , TuFa; Tongdecharoen, Wisute; Tasnaina, Nopporn (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: This research was an intensive training program for badminton reserve players to select matches. The objective was to 1) construct an intensive training program for badminton reserve players before team selection matches,2) study the effect of an intensive training program for badminton reserve players before team selection matches on physical fitness and badminton skills, 3) compare physical fitness and badminton skill within the experimental group between the pre-test, after week 4, and post-test, and 4) to compare badminton skills and mental fitness between pre-match and post-match competitions. Materials and Methods: This quasi-experimental research involved the purposive sampling method of 26 youth badminton members from the Dongguan Xianghong Badminton Club in Guangzhou, dividing the subjects into specific events of badminton competition, such as men's singles, women's singles, men's doubles, women's doubles, and mixed doubles. The intensive training program was developed by the researcher, content validated with an index of item objective congruence (IOC) of 0.83, that with the first six weeks, they trained in technical, physical fitness, and strength training; in the last 2 weeks, they trained specific techniques and tactics, eight weeks duration, five days per week. All subjects were examined before training on the pre-match competition and mental fitness, then the pre-test on badminton skills and physical fitness. They conducted the training program, the test after week 4, and the post-test. In the final, they were examined on the post-match competition and mental fitness. Data analysis, the mean was compared between the pre-test, after week 4, and post-test with one-way ANOVA repeated measurement, and Bonferroni pairwise post hoc. The mean comparison of match competition between pre-match with post-match competition and mental fitness was conducted by t-test dependent. Results: (1) Mean comparison between pre-match competitions and post-match, all badminton skills and mental fitness showed significant differences. (2) Mean comparison of badminton skills between pre-test, after weeks 4 and post-test, all of pairwise were significant differences. And (3) Mean comparison of physical fitness between the pre-test, after weeks 4 and post-test, all of pairwise were significant differences. Conclusion: An intensive Training program for Badminton can improve badminton skills, physical fitness, and mental fitness for reserve players before a team selection match.